Multimorbidity Is Associated With Pain Over 6 Years Among Community-Dwelling Mexican Americans Aged 80 and Older - Milani, Sadaf Arefi; Raji, Mukaila A.; Kuo, Yong-Fang; Lopez, David S.; Markides, Kyriakos S.; Al Snih, Soham (Frontiers in Pain Research, 2022)
Introduction Multimorbidity, the co-occurrence of two or more chronic conditions, is common among older adults and is associated with decreased quality of life, greater disability, and increased mortality. Yet, the association of multimorbidity with pain, another significant contributor to decreased quality of life, has not been widely studied. This is especially understudied among very old (aged ≥ 80) Mexican Americans, a fast-growing segment of the United States (US) population. Objective To assess the association of multimorbidity with pain in very old Mexican Americans, over six years of follow-up. Methods We used data from Waves 7 (2010/2011) to 9 (2015/2016) of the Hispanic Established Populations for the Epidemiologic Study of the Elderly, a longitudinal study of older Mexican Americans residing in the Southwestern US. Multimorbidity was defined as reporting two or more chronic health conditions. Pain was defined as (1) pain on weight-bearing, (2) pain in back, hips, knees, ankles/feet, legs, entire body, or two or more locations, and (3) pain that limits daily activities. We use generalized estimation equations to estimate the odds ratio of pain as a function of multimorbidity over 6 years. Results At baseline (n = 841), 77.3% of participants had multimorbidity. Those with multimorbidity had greater odds [2.27, 95% confidence interval (CI): 1.74, 2.95] of reporting pain on weight-bearing over time, compared to those without multimorbidity. Also, those with multimorbidity had 2.12 times the odds of reporting pain that limited their daily activities (95% CI: 1.61, 2.78) compared to those without multimorbidity. Lastly, those with multimorbidity had higher odds of reporting pain in their back, knee, ankles/feet, legs, hips, entire body, or two or more locations, compared to those without multimorbidity. Conclusions Those with multimorbidity consistently had higher odds of all types of pain, highlighting the need for early management of pain among those with multiple chronic conditions and complex health needs. This is especially important among very old Mexican Americans, who have a high burden of chronic health conditions.